2017
DOI: 10.1038/s41598-017-03765-y
|View full text |Cite
|
Sign up to set email alerts
|

Secretory laccase 1 in Bemisia tabaci MED is involved in whitefly-plant interaction

Abstract: The whitefly Bemisia tabaci is a phloem-feeding pest that lives predominantly on herbaceous species and causes serious damage to hosts. Whitefly saliva is thought to contain proteins that modulate plant defences and facilitate feeding. A predicted secreted protein, laccase 1 (LAC1), was found in the salivary gland transcriptome of B. tabaci and might be existed in the watery saliva of B. tabaci. As LAC1 has a potential role in detoxification of secondary plant compounds in insects, we speculated that it may pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 50 publications
(58 reference statements)
1
34
0
Order By: Relevance
“…Yang et al. () also found that Lac 1 had the highest levels of expression in the fourth instar and adult stage of B. tabaci .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Yang et al. () also found that Lac 1 had the highest levels of expression in the fourth instar and adult stage of B. tabaci .…”
Section: Discussionmentioning
confidence: 90%
“…First, Laccase 1 was obtained from S. avenae in our study, and three different conserved copper domains, Type‐1 (T1), Type‐2 (T2), and Type‐3 (T3) (Dwivedi, Singh, Pandey, & Kumar, ), were found in the sequence, indicating that SaLac 1 is a member of the blue copper‐containing polyphenol oxidase family and has oxidative activity. Studies demonstrate that Lac 1 is a secreted protein, and laccase activity has been detected in the watery saliva of B. tabaci and N. cincticeps (Hattori, Konishi, Tamura, Konno, & Sogawa, ; Yang et al., ). However, in our study, Lac 1 in S. avenae was predicted as attached to the exterior of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The candidate effector cDNAs encode proteins annotated as follows: 2G5, an unknown protein, and 6A10, large subunit ribosomal RNA ( Figure 6A). The expression levels of these genes did not significantly differ from that of the positive control, Lac1 (Figure 6A), encoding a recently identified whitefly effector (Yang et al, 2017). Collectively, of the three clones, only clones 2G5 and 6A10 represent solid candidate whitefly effectors.…”
Section: In Silico Analysis Of Effector Expression In Whiteflymentioning
confidence: 91%
“…Whitefly saliva is thought to contain proteins that modulate plant defense responses and facilitate feeding. Secreted whitefly laccase 1 (LAC1) and small RNAs have been identified and are thought to help the insect overcome plant immunity responses (van Kleeff et al, 2016;Yang et al, 2017). …”
Section: Introductionmentioning
confidence: 99%